(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The purpose of this study was to determine whether pictures can improve students’ writing skills and classroom conditions. The subjects of this study were students of class X at SMK NEGRI 1 Subang. The research method used is classroom action research. This research was conducted in two cycles. Each cycle consists of four steps: planning, action, observation and reflection. To collect qualitative data, the researcher used field notes, photos and interviews. To collect quantitative data, researchers conducted tests. The tests carried out were pretest and posttest. To analyze the qualitative data, the researcher used an interactive model of data analysis. For quantitative data, the researcher analyzed the test mean scores to compare the differences between the pre-test and post-test. The results showed that teaching writing skills using pictures could improve students’ writing skills and classroom conditions. The increase in the average score indicates that there is an increase in students’ writing skills. Therefore, it can be concluded that teaching writing skills by using pictures can improve students’ writing skills.